Small and medium-sized towns in Switzerland: economic heterogeneity, socioeconomic performance and linkages - Meili, Rahel; Mayer, Heike (ERDKUNDE, 2017)
Knowledge about economic characteristics and development dynamics of small and medium-sized towns (SMSTs) is scarce. The aim of this article is to present insights into economic characteristics and development dynamics of SMSTs in Switzerland and to conceptualize the linkages of SMSTs with neighboring centers and hinterlands. SMSTs in Switzerland are independent jurisdictions that are in charge of their economic development strategies, tax base, etc, which can shape their socio-economic characteristics independently of the larger urban agglomeration they belong to. This circumstance makes them especially interesting for research particularly regarding the economic heterogeneity, socioeconomic performance and functional linkages these SMSTs have. The article presents seven types of SMSTs that have different economic characteristics and socio-economic dynamics. The types were built using cluster analysis. The typology shows that SMSTs can have different economic characteristics and development dynamics despite being embedded in the same regional context. For analyzing relationships between cluster membership and linkages to neighboring centers, we carried out an analysis of variance. It can be inferred that the intensity of linkages of SMSTs vary according to the type of SMSTs.